A Screening strategy for selection of Anti-HIV-1 Integrase and anti-HIV- 1 Protease Inhibitors from extracts of Indian Medicinal plants - Chaitra Narayan L; Ravishankar Rai V; Supinya Tewtrakul (International Journal of Phytomedicine, 2011)
Ethanolic and water extracts from six species of Indian medicinal plants mainly distributed in the region of Western Ghats, India such as Morinda citrifolia (leaf), Garcinia indica (leaf), Garcinia cambogia (leaf), Salacia oblonga (leaf), Coccinium fenestratum (stem bark) and Calophyllum inophyllum (bark) were tested for their inhibitory activities against two prime enzymes of HIV which are HIV-1 protease (HIV-PR) and HIV-1 integrase (HIV-IN). The results revealed that the ethanolic and water extract of the bark extract of Calophyllum inophyllum exhibited potent anti-HIV-IN activity with IC50 values of 9.8 and 5.6 μg/ml, respectively. Whereas those for anti-HIV-1 PR effect were found to be 63.8 and 16.3 μg/ml, respectively. This result strongly supports the basis for the use of C. inophyllum for AIDS treatment by local traditional practitioners of Ayurveda and Unani system of Indian medicine and it is the first report on HIV-1 Protease and HIV-1 Integrase enzyme inhibition by this plant extract.